The Influence of Work Demands and Rewards on Hospital Service Quality through Employee Satisfaction - Imron, Ali; Setyawan, Anton Agus; Romaniyanto, Romaniyanto; Sumarwoto, Tito; Guntoro, Amed Gatut; Romadhon, Yusuf Alam (Jurnal Manajemen Bisnis dan Kewirausahaan, 2026)
This study investigates how job demands and job rewards influence hospital service quality, and whether employee satisfaction mediates these relationships among staff at Prof. Dr. R. Soeharso Orthopedic Hospital, Surakarta. Using an explanatory quantitative design, Likert-scale questionnaires were collected from 235 medical and non-medical employees (n=235) through voluntary response sampling and analyzed with PLS-SEM (SmartPLS) to test a model comprising job demands (X1), job rewards (X2), employee satisfaction (Z), and service quality (Y), operationalized with demand, reward, satisfaction, and SERVQUAL-based service quality indicators. The measurement model met adequacy criteria (AVE>0.50; composite reliability=0.875–0.935; Cronbach’s alpha>0.80) and showed acceptable collinearity (VIF<5). In the structural model, job demands had a negative but non-significant direct effect on service quality (β=-0.025; t=0.415; p>0.05), while job rewards had a positive, significant direct effect (β=0.281; t=3.405; p=0.001). Job demands significantly reduced employee satisfaction (β=-0.198; t=3.455; p=0.001), whereas job rewards strongly increased satisfaction (β=0.759; t=26.836; p<0.001). Employee satisfaction positively predicted service quality (β=0.389; t=4.210; p<0.001) and mediated both exogenous variables’ effects on service quality; effect-size results indicated a large contribution of rewards to satisfaction (f²=1.564). The model explained 63.3% of the variance in employee satisfaction (R²=0.633; Q²=0.439) and 40.5% in service quality (R²=0.405; Q²=0.280). Theoretically, the findings extend job demands–resources logic in a hospital context by evidencing satisfaction as a key mechanism linking work conditions to perceived service quality. Practically, hospital managers should calibrate workloads and institutionalize fair financial and non-financial rewards to sustain satisfaction and improve service delivery. Overall, the study shows that reward strengthening and demand management are strategic levers for consistently high-quality hospital services.